Analisis Perkembangan Program Rolasan Dalam Penerapan Smart City Di Dinas Komunikasi Dan Informatika Kabupaten Klaten - Argata, Sisca Tyas; Wirawan, Riska (Solidaritas, 2025)
The Rolasan Program is a form of Smart City initiative in Klaten Regency which aims to provide information to the public through digital platforms, especially YouTube and Spotify. The research aims to analyze the development of the Rolasan Program in implementing the Smart City concept at the Klaten Regency Communication and Informatics Office. This study uses Richardus Indrajit's theory, namely content development, competency building, connectivity, cyber laws, citizen interfaces, and capital. This research method is descriptive qualitative aimed at analyzing and describing the development of the Rolasan program. Data collection was carried out by interview, observation and documentation. The data analysis technique used is the analysis technique according to Miles Huberman. The results of the study showed that although the Rolasan program has good potential in improving public services, there are still several challenges. In addition, of the six indicators carried out by researchers, the Rolasan program was not satisfactory.